Anti-Mosquito Spray Based on Carbon Nanodots from Durian Peel Waste - Ufairah, Ghina Syifa; Rukasih, Tina; Yuflihza, Zaharani; Dwandaru, Wipsar Sunu Brams (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
The accumulation of organic waste can cause various diseases and environmental pollution. One of the diseases caused by this is Dengue Hemorrhagic Fever (DHF). Organic waste such as durian peel waste contains carbon, which can be processed into carbon nanodots (C-dots). The C-dots from durian peel waste can be used as a basic ingredient for mosquito repellent spray because durian peel contains essential oils, flavonoids, saponins, and tannins, which are toxic to mosquitoes. The synthesis of C-dots can also reduce environmental pollution due to durian peel waste. The purpose of this study was i) to prepare and characterize C-dots from durian peel waste using UV-Vis and PSA tests, and ii) to identify the effect of the C-dots solution in a mosquito repellent test in order to determine the ability of the anti-mosquito spray. This was an experimental study on the preparation of C-dots from durian peel waste using the two-steps low heating (TSLH) method. The anti-mosquito spray was made of 3 ratios of C-dots mass to distilled water volume, i.e.: (0.1 g : 200 ml); (0.2 g : 200 ml); and (0.3 g : 200 ml). Based on the results of the UV-Vis and PSA characterizations, it was found that the absorption peaks of the C-dots were at the wavelength interval of 288–332 nm and the sizes of the C-dots were 178.6 nm (69.3%) and 54.1 (20%). The mosquito repellent test showed that the anti-mosquito spray could repel and eradicate mosquitoes at the best ratio of (0.1 g C-dots : 200 ml of distilled water) with the highest mosquito’s mortality of 11 mosquitoes in 17 minutes and 29 seconds. This proves that the C-dots from durian peel waste can be used as an anti-mosquito spray.